Teacher Empowerment through International Communities of Practice - Doyran, Feyza (My University, 2018)
The qualities of 21st century students as well as teachers have been analyzed in many recent studies and the results show that the new generation students’ needs considerably differ from the previous generations. In a recent study conducted (Doyran, 2018) with nineteen teachers attending Educational Administration and Planning graduate program at a foundation university in Istanbul revealed that among the most common behavior problems of new generation students faced by the teachers are: Rude language use, being irresponsible, lack of cultural values, lack of motivation for school, disruptive behaviors, being spoiled by the families, having no rules, unorganized home atmosphere, tendency for violence, aggression and seeking continuous care and attention. Teachers mostly see the roots of these problems as the families/parents. When asked about how they overcome these problems, the results showed that they need to be empowered with different strategies to deal with these specific needs. The results of another research conducted by the same researcher with thirty-four teachers on interpersonal communication problems of teachers also supported the results of the previous study. Teachers pointed out that the most frequently experienced problems the teachers go through are: behavior problems of the new generation students, misinterpretation of words/language, judgmental behaviors and misunderstanding each other. In this presentation, issues related to the new demands, challenges and expectations of teacher education programs will be discussed and the possibilities of creating international communities of practice to support and empower teachers will be discussed.
Keywords: Teacher Empowerment; Problem Behaviors of New Generation Students; Prevention and Overcoming Strategies; Positive Classroom Atmosphere; Creating International Communities of Practice